Hydraulic Engineering in Dam-Type Tidal Power Plant - Alexander Erkhov (Global Journals of Research in Engineering, 2024)
During the years of Soviet power several tidal power plants were procured on the territory of the RSFSR but only one was built - experimental despite several promising projects - interest in TPP fell Economic and demographic trends suggest an impending shortage of energy resources in the world and now in the foreign press they are increasingly discussing the results of the work of existing TPP studying the options for the layout of stations the advantages and disadvantages of various types of hydraulic turbines the development of the theory of tidal power plants is a problem of energy construction science and construction sciences as well as engineering hydrology geology geodesy geotechnics ecology hydraulics etc at each stage of the life cycle of significant in different ways - before the commissioning of the structure in the priority of engineering and construction sciences and the emphasis in this work is on the main aspect of the life cycle of the design stage while the scientific novelty is to designate the engineering hydraulics of TPP as a complex problem of system analysis